Kinetic small angle neutron scattering of the skyrmion lattice in MnSi. (25th July 2016) - Mühlbauer, S; Kindervater, J; Adams, T; Bauer, A; Keiderling, U; Pfleiderer, C
Abstract: We report a kinetic small angle neutron scattering (SANS) study of the skyrmion lattice (SL) in MnSi. Induced by an oscillatory tilting of the magnetic field direction, the elasticity and relaxation of the SL along the magnetic field direction have been measured with microsecond resolution. For the excitation frequency of 325 Hz the SL begins to track the tilting motion of the applied magnetic field under tilting angles exceeding α c ≳ 0.4 ° . Empirically the associated angular velocity of the tilting connects quantitatively with the critical charge carrier velocity of ∼ 0.1 mm s − 1 under current driven spin transfer torques, for which the SL unpins. In addition, a pronounced temperature dependence of the skyrmion motion is attributed to the variation of the skyrmion stiffness. Taken together our study highlights the power of kinetic SANS as a new experimental tool to explore, in a rather general manner, the elasticity and impurity pinning of magnetic textures across a wide parameter space without parasitic signal interferences due to ohmic heating or Oersted magnetic fields.